Jane E. Francis and Anna Kouremenos (eds) Roman Crete. New Perspectives - Karambinis, Michalis (Journal of Greek Archaeology, 2019)
This volume was instigated by a panel on Roman Crete presented at the Roman Archaeology Conference in Frankfurt, Germany in March 2012. The current book comprises a selected number of papers from the RAC panel, to which are added seven other articles. Totally, the volume is consisting of 13 articles, plus a foreword written by Hugh Sackett, and an introduction and an afterword, where the editors present an account of the previous archaeological and historical research on Roman Crete, summarize the outputs of the volume papers, and propose directions for future research.